Incorporating Pet Fish Into Your Small Animal Practice - Ruth Francis-Floyd (EDIS)
There are several factors that make it advantageous to consider adding pet fish medicine to your small animal practice at the present time. Over the past five to ten years, some veterinary schools have begun to incorporate aquatic animal medicine into their curricula. Many recent graduates have had some level of exposure to fish medicine as part of their veterinary education, and some individuals have had one or more intensive classes and/or clinical rotations in fish medicine. In addition, some veterinary colleges and national meetings now offer continuing education opportunities for graduate veterinarians in this area. This document is VM147, one of a series of the Veterinary Medicine-Large Animal Clinical Sciences Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Original publication date August 12, 2003.